Financial Determinants, Company Performance, and Tax Rate on Sustainable Growth - Elia Rossa; Adler Haymans Manurung; Nera Marinda Machdar; Tutty Nuryati (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Sustainable company growth has increasingly become a strategic priority in the post-pandemic era, where businesses must balance profitability with Environmental, Social, and Governance (ESG) responsibilities. While previous studies have focused on the direct impact of financial determinants, limited research in emerging markets has explored the mediating role of company performance and the moderating influence of tax rates in shaping sustainable growth. This study investigates the mediating effect of company performance and the moderating effect of tax rate on the relationship between financial determinants and company sustainable growth. Using Structural Equation Modeling (SEM) with Partial Least Squares approach, the study analyzed 672 observations from Indonesian Stock Exchange-listed companies during 2018-2024. Financial determinants include capital structure, liquidity, profitability, and company size, while company performance is measured by Tobin’s Q and tax rate by effective tax rate. Results reveal that profitability has the strongest positive influence on sustainable growth, while capital structure shows significant indirect effect through company performance mediation. Tax rate significantly moderates the relationship between capital structure and profitability on sustainable growth. The study provides comprehensive understanding of complex relationships in corporate finance, contributing to strategic financial management and policy formulation in emerging markets.